The Loss of Mitochondrial Quality Control in Diabetic Kidney Disease - Dai, Wenni; Lu, Hengcheng; Chen, Yinyin; Yang, Danyi; Sun, Lin; He, Liyu (Frontiers in Cell and Developmental Biology, 2021)
Diabetic kidney disease (DKD) is the predominant complication of diabetes mellitus (DM) and the leading cause of chronic kidney disease and end-stage renal disease worldwide, which are major risk factor for death. The pathogenesis of DKD is very complicated, including inflammation, autophagy impairment, oxidative stress and so on. Recently, accumulating evidence suggests that the loss of mitochondrial quality control exerts critical roles in the progression of DKD. Mitochondria are essential for eukaryotic cell viability, but are extremely vulnerable to damage. The mechanisms of mitochondrial quality control act at the molecular level and the organelle level, including mitochondrial dynamics (fusion and fission), mitophagy, mitochondrial biogenesis and mitochondrial protein quality control. In this review, we summarize current knowledge of the role of disturbances in mitochondrial quality control in the pathogenesis of DKD and provide potential insights to explore how to delay the onset and development of DKD.